The Comparison of Progressive Muscle Relaxation Frequency on Anxiety, Blood Pressure, and Pulse of Haemodialysis Patients - Kusnanto Kusnanto; Maulana Arif Murtadho; Lilik Herawati; Hidayat Arifin (Jurnal Ners, 2019)
Introduction: Haemodialysis is one of the kidney replacements therapies, but, as it cannot wholly replace kidney function, it still causes complications such as increased blood pressure and pulse which can lead to anxiety for the patient. The purpose of this study was to explain the effect of Progressive Muscle Relaxation (PMR) on anxiety, blood pressure and pulse in haemodialysis patients.Methods: The study design was a true pre-post-test control group design experiment. The total sample was 105 haemodialysis patients taken by purposive sampling technique and divided into two intervention groups and one control group. The independent variable was PMR, and the dependent variables were anxiety, blood pressure and pulse. Data were obtained using a questionnaire and analysed using the Kruskal Wallis Test and Mann-Whitney U test with a significance level <0.05.Results: The results of the PMR two times per week group analysis for one month showed a significant influence on anxiety (p=0.000), blood pressure (p=0.000), and pulse rate (p=0.000). Mann-Whitney U Test Results showed a significant effect on anxiety (p=0.004), blood pressure (p=0.000), and pulse (p=0.000).Conclusion: Haemodialysis patients who performed PMR interventions showed a promising outcome on a decrease in anxiety, blood pressure and pulse. The regular application of PMR interventions can control vital signs in patients undergoing haemodialysis